If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -5x = 1 + -2(1 + x) 17 + -5x = 1 + (1 * -2 + x * -2) 17 + -5x = 1 + (-2 + -2x) Combine like terms: 1 + -2 = -1 17 + -5x = -1 + -2x Solving 17 + -5x = -1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 17 + -5x + 2x = -1 + -2x + 2x Combine like terms: -5x + 2x = -3x 17 + -3x = -1 + -2x + 2x Combine like terms: -2x + 2x = 0 17 + -3x = -1 + 0 17 + -3x = -1 Add '-17' to each side of the equation. 17 + -17 + -3x = -1 + -17 Combine like terms: 17 + -17 = 0 0 + -3x = -1 + -17 -3x = -1 + -17 Combine like terms: -1 + -17 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| c+12+b+7= | | (7.32)(6.8)= | | 4*10=27.5*x | | (n-2)=36 | | 4*x=27.5*10 | | 20-x=2(x-15)-1 | | 2(4y-2)+9=4(3y+2)+7 | | 8v+6-9= | | onethird(9x-3)=-10 | | m+17=3+1 | | -7(-3)(2)= | | 81+4w=5w-27 | | 2(9n-1)+7(n+6)= | | -1+5x=-41 | | -1+5=-41 | | 9s=33-3s | | 4x+4=9+8 | | 25x^2-30x+13=0 | | 2x^3-14x^2+28x= | | 3(x+1)=4(x-8) | | 8t=55+4t | | (9+2(5x))=39 | | y=x-6*z | | 25-6p=4p | | 4x-19=27 | | 11x-12=5x+48 | | x^5-2x^3-8x=0 | | 4r+-8=10r+12 | | 4x^3-16x^2+20x= | | 5(3x)+2=32 | | (4+l)+2mi=9+14i | | (4x^2-2)(2x^2+3)= |